Modifikasi Vigenere Cipher Menggunakan Grup Simetri untuk Mengamankan Pesan Teks - Cahyanti, Niken Dwi; Turmudi, Turmudi; Khudzaifah, Muhammad (Jurnal Riset Mahasiswa Matematika, 2023)
Cryptography is widely used to overcome information security problems that are exchanged on the internet network. One of the algorithms in cryptography is the Vigenere Cipher, the algorithm is known as a robust method and is not easily solved. However, the Vigenere Cipher algorithm has a weakness, namely the key is short and is used repeatedly. Therefore, it is necessary to modify the Vigenere Cipher. The purpose of this study is to determine the modification of the Vigenere Cipher using a symmetric group and also to determine the level of security of the encryption results of Vigenere Cipher modification when compared to the Vigenere Cipher. The results obtained from this research is a new algorithm of the modification process of the Vigenere Cipher using symmetric groups. The modified Vigenere Cipher algorithm is proven to be stronger than the Vigenere Cipher. This is because the plaintext is scrambled first using a symmetric group encoding, so that the actual plaintext is safe against attacks by the Kasiski method and exhaustive key search. In addition, the resulting new algorithm also supports the use of capital letters, lowercase letters, numbers, and symbols.